2015
DOI: 10.1016/j.jcmgh.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Neuron Imbalance and Proximal Dysmotility in Ganglionated Intestine of the Sox10Dom/+ Hirschsprung Mouse Model

Abstract: Background & Aims In Hirschsprung disease (HSCR), neural crest-derived progenitors (NCPs) fail to completely colonize the intestine so that the enteric nervous system (ENS) is absent from distal bowel. Despite removal of the aganglionic region, many HSCR patients suffer from residual intestinal dysmotility. To test the hypothesis that inappropriate lineage segregation of NCPs in proximal ganglionated regions of the bowel could contribute to such postoperative disease, we investigated neural crest (NC)-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 46 publications
4
28
1
Order By: Relevance
“…Our study excluded patients with total colonic aganglionosis, but a similar trend was seen toward a higher incidence of constipation in patients with a longer length of aganglionosis. Studies in mice have suggested that the extent of neuronal subtype imbalance also correlates with the length of aganglionosis [8]; however, we found no correlation between the proportion of NOS neurons and the length of bowel resected. In addition, studies have shown that disturbances in NOS expression are greater in older HD mice [9], but we found no similar correlation between NOS and age in our patients.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Our study excluded patients with total colonic aganglionosis, but a similar trend was seen toward a higher incidence of constipation in patients with a longer length of aganglionosis. Studies in mice have suggested that the extent of neuronal subtype imbalance also correlates with the length of aganglionosis [8]; however, we found no correlation between the proportion of NOS neurons and the length of bowel resected. In addition, studies have shown that disturbances in NOS expression are greater in older HD mice [9], but we found no similar correlation between NOS and age in our patients.…”
Section: Discussioncontrasting
confidence: 93%
“…NOS+ neurons are one of the first subtypes to appear in embryonic mouse colon [20], and failure of neuronal maturation to progress normally may result in an overabundance of NOS+ neurons. In previous studies in mouse models of HD, neuronal subtype imbalance was found to be limited to the mid and distal colon and was normal in proximal colon and small bowel [8, 9]. The extent of neuronal abnormality in HD patients is not yet known and warrants further study, as this knowledge is essential to determine the appropriate length of resection and to predict functional outcome after pullthrough.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that hedgehog signaling is required for the normal migration of enteric neural progenitors and glial cell generation through Sox10 regulation (Liu et al, 2015; Ngan et al, 2011). In Sufu mutants, the networks of enteric ganglia were disorganized and neuron:glial cell ratios were reduced, a defect reminiscent of that recently described in Sox10 and Raldh1, -2, and -3 mutants (Musser et al, 2015; Wright-Jin et al, 2013). Because mice lacking Sufu in neural crest cells die before the gut is completely colonized by ENCCs, the authors were however not able to determine whether loss of Sufu results in an absence of neurons in the distal bowel and thus a HSCR-like phenotype.…”
Section: Molecular Mediators That Control Ens Development and Maturatsupporting
confidence: 52%
“…While transcription factors that participate with Sox10 auto-regulation have been identified (Wahlbuhl et al, 2012), cofactors that participate with Sox10 in regulation of Ednrb are not yet known. Analysis of Sox10 Dom mouse mutants revealed that alterations in this transcription factor not only lead to distal aganglionosis, but can also disrupt normal proportions of neuron subtypes in ganglionated small intestine that lead to deficits in intestinal transit (Musser et al, 2015). Similarly, Zeb2 plays essential roles in enteric neurogenesis by promoting ENCC proliferation and early migration within the fetal bowel (Stanchina et al, 2010; Van de Putte et al, 2003) via interactions with Sox10.…”
Section: Molecular Mediators That Control Ens Development and Maturatmentioning
confidence: 99%